Efficient replication, integration, and packaging of retroviral vectors with modified long terminal repeats containing the packaging signal. - Joshi, S (1990)
Retroviral vectors were modified to contain packaging (psi) signals of varying lengths (nucleotides 211-355, 211-565, or 211-1039 of MoMuLV RNA) between the U3-r and U5 sequences of their 5' long terminal repeat (LTR). For the vector MoTN-PR3, containing the full length 211-1039 nucleotide-long psi signal within the 5' LTR, replication, integration, and packaging were almost as efficient as for the original unmodified vector. This result confirmed that the 211-1039 nucleotide-long sequence from the MoMuLV RNA is sufficient and necessary to allow efficient packaging of RNAs. In addition, an important site was revealed where insertion of foreign DNA sequences of up to 829 nucleotides can be made within the 5' LTR, between U3-r and U5 sequences, without affecting viral replication, integration, or packaging.